1996
DOI: 10.1021/ac9605915
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation by Mass Spectrometry of a Trisulfide Variant in Methionyl Human Growth Hormone Biosynthesized inEscherichia coli

Abstract: A sulfur-containing compound found in acid hydrolysates of proteins was identified 30 years ago as a trisulfide: bis-(2-amino-2-carboxyethyl) trisulfide (cysteine2S3). At that time, studies concerning the chemistry of sulfur-transferring enzyme systems suggested that cysteine2S3 also existed in biological systems. Two decades later, a cystine trisulfide structure was postulated in the regulator protein molecule for the activation of delta-aminolevulinate synthetase. Recently, a trisulfide bond was reported to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…[7,8] More recently, Tous et al reported the occurrence of a nonreducible thioether bridge between the light and heavy chains of different IgG1 monoclonal antibodies. [9] However, the present article is to our knowledge the first description of a thioether-containing hGH variant.…”
Section: Discussionmentioning
confidence: 99%
“…[7,8] More recently, Tous et al reported the occurrence of a nonreducible thioether bridge between the light and heavy chains of different IgG1 monoclonal antibodies. [9] However, the present article is to our knowledge the first description of a thioether-containing hGH variant.…”
Section: Discussionmentioning
confidence: 99%
“…For proteins, the modification was first discovered in cysteine bridges (Cys 53 -Cys 165 and Cys 182 -Cys 189 ) of biosynthetic human growth hormone produced in Escherichia coli [1,2] and in the non-recombinant protein Cu-Zn superoxide dismutase [3]. More recently, trisulfides have been identified and characterized in recombinant monoclonal antibodies (mAbs) of all immunoglobulin G (IgG) sub-classes [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, reports of trisulfide formation when proteins are exposed to alkaline treatments have also appeared [54]. The occurrence of a trisulfide moiety in a recombinant human growth hormone has been established by mass spectrometry [55,56]. The high reactivity of the species formed when disulfides are exposed to basic media prompted us to re-examine the various products generated upon disulfide cleavage, by mass spectrometry.…”
mentioning
confidence: 99%